INTEGRATION OF JURAN'S TRILOGY, DEMING'S QUALITY CYCLE AND DMAIC METHODOLOGY IN THE DEVELOPMENT OF MANAGEMENT WITH QUALITY COST METHODOLOGY - Velkoska, Cvetanka (International Scientific Journal Vision, 2022)
This paper presents systematized approach to introducing and implementing a management system with quality costs, with a development of a management methodology using quality costs which, in a structured and systematic manner includes all relevant procedures (algorithms), with a view fully expressing the benefits and usefulness of the quality costs. The methodological approach includes the algorithm for introducing and implementing the management system with quality costs, the algorithm for the selection of a relevant quality costs approach and model, the quality costs identification and categorization algorithm, the quality costs measuring algorithm, as well as the quality costs management algorithm and the algorithm for management with quality costs. The scientific contribution of this paper involves the integration of the three known methodologies used in quality management: Juran's trilogy, Deming's quality cycle – PDCA, and the DMAIC methodology, in the development of the methodology for quality management with quality costs, aimed at improving the effectiveness of the management system with quality costs and the sustainability of the company.